2017
DOI: 10.1038/srep44266
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Roles of Receptor-Associated Prorenin System in Idiopathic Epiretinal Membrane

Abstract: Receptor-associated prorenin system (RAPS) refers to the pathogenic mechanism whereby prorenin binding to (pro)renin receptor [(P)RR] dually activates tissue renin-angiotensin system (RAS) and RAS-independent signaling via (P)RR. The aim of this study is to determine the association of RAPS with idiopathic epiretinal membrane (iERM). Reverse transcription-PCR indicated the expression of RAPS components, including (P)RR and Ang II type 1 receptor (AT1R), in iERM tissues and human Müller glial cell line. Double-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 30 publications
(67 reference statements)
1
16
0
Order By: Relevance
“…Our clinical sample data also revealed (P)RR involvement in retinal angiogenesis and systemic inflammation in patients with PDR, showing a close association of RAPS with the molecular mechanism of PDR [37][38][39]. Moreover, increasing evidence has suggested RAPS activation in various human eye disorders including age-related macular degeneration [40], idiopathic epiretinal membrane [41], noninfectious uveitis [42], and conjunctival lymphoma [43].…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Our clinical sample data also revealed (P)RR involvement in retinal angiogenesis and systemic inflammation in patients with PDR, showing a close association of RAPS with the molecular mechanism of PDR [37][38][39]. Moreover, increasing evidence has suggested RAPS activation in various human eye disorders including age-related macular degeneration [40], idiopathic epiretinal membrane [41], noninfectious uveitis [42], and conjunctival lymphoma [43].…”
Section: Introductionsupporting
confidence: 63%
“…In the mouse model of diabetic retinopathy, leukocyte adhesion to the retinal vasculature was revealed to be governed independently by both AT1R and (P)RR [17,32]. Molecules induced via (P)RR downstream pathway and their cellular sources were reported to include monocyte chemotactic protein 1 in brain capillary endothelial cells [34], vascular endothelial growth factor A in macrophages [34] and retinal microvascular endothelial cells [37], transforming growth factor-β1 in retinal pigment epithelial cells [40], and fibroblast growth factor 2 in Müller glial cells [41]. (P)RR signaling would thus lead to various pathologic conditions such as inflammation, angiogenesis, and fibrosis, depending on different cellular reactions in diabetic retinopathy [37], age-related macular degeneration [40], and idiopathic epiretinal membrane [41].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our findings, a blockade of (P)RR is theorized to inhibit the cascade of events crucial in various vascular abnormalities represented by inflammation and angiogenesis. Aliskiren, a direct renin inhibitor, competitively inhibited the renin enzymatic activity of both renin and activated prorenin through interaction with (P)RR in vitro ; however, RAS inhibitors including aliskiren have no efficacy of blocking (P)RR's own downstream signals.…”
Section: Development Of a Novel Single‐strand Rna Interference Therapmentioning
confidence: 70%
“…These results show that the close link between the RAPS components and CCL2/MCP‐1 levels would validate the pathogenic role of (P)RR that contributes to inflammation in human uveitis. Furthermore, we have shown that RAPS activation contributes to the molecular pathogenesis, including inflammation, angiogenesis and fibrosis, of other ocular disorders, such as conjunctival lymphoma and idiopathic epiretinal membrane.…”
Section: (Pro)renin Receptor In Uveitismentioning
confidence: 99%
“…To investigate which pro-fibrotic cytokine can induce mesenchymal (EMT-like) changes in human Müller glial cells, we stimulated MIO-M1 cells with various cytokines and growth factors known for their fibrogenic activity and/or their protein expression in the iERM tissue 12,16,17 , and analyzed mRNA expression levels of several EMT-related molecular markers by real-time quantitative PCR. Smooth muscle protein (SM)22, also known as transgelin encoded by the TAGLN gene, is an actin-binding cytoskeletal protein recently utilized as another marker for myofibroblasts and mesenchymal cells, on top of conventionally used α-SMA 1820 .…”
Section: Resultsmentioning
confidence: 99%